Cover Image. Issue 5 (May 2017) - Shah, S. R.; Chowdhury, A.; Mehta, R.; Kapoor, D.; Duseja, A.; Koshy, A.; Shukla, A.; Sood, A.; Madan, K.; Sud, R.; Nijhawan, S.; Pawan, R.; et al.
Abstract : The cover image, by S. R. Shah et al., is based on the Original Article Sofosbuvir plus ribavirin in treatment‐naïve patients with chronic hepatitis C virus genotype 1 or 3 infection in India, DOI10.1111/jvh.12654 .